Ninth IEEE International Conference on Fuzzy Systems. FUZZ- IEEE 2000 (Cat. No.00CH37063)
DOI: 10.1109/fuzzy.2000.839201
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical fuzzy logic control of a double inverted pendulum

Abstract: This paper uses dynamical hierarchical control to stabilize a double inverted pendulum. Hamilton's principle is introduced to build the dynamic model of the system, The double inverted pendulum is decomposed into subsystems. Fuzzy logic controllers are designed for each subsystem at the lower level of the hierarchy. At the higher level a fuzzy logic based coordinator is built up to supervise the complete system. Computer simulation using the Matlab Fuzzy Logic Toolbox compares the fuzzy logic controller (FLC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The method is developed for a wide class of control systems and the feasibility of the method is demonstrated by developing a two-layered HFS for controlling the inverted pendulum system. Other examples of hierarchical fuzzy control applied to the inverted pendulum system can be found in [41][42][43][44][45][46][47]. Related studies, but not applied to the inverted pendulum system, can be found in [47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Related Workmentioning
confidence: 99%
“…The method is developed for a wide class of control systems and the feasibility of the method is demonstrated by developing a two-layered HFS for controlling the inverted pendulum system. Other examples of hierarchical fuzzy control applied to the inverted pendulum system can be found in [41][42][43][44][45][46][47]. Related studies, but not applied to the inverted pendulum system, can be found in [47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Related Workmentioning
confidence: 99%
“…Combination of hierarchical fuzzy control and sliding mode was presented by Lin and Mon [4]. Other examples of hierarchical fuzzy control applied to the inverted pendulum system can be found in [5] and [6]. Chang et al [7] used the inverted pendulum system as a case study for the robust fuzzy-model-based sliding mode.…”
Section: Related Workmentioning
confidence: 99%
“…The inverted pendulum is one of standard systems for demonstration of high efficient advanced control algorithms. A large number of publications are dealing with erecting and balancing the inverted pendulum using state space controllers, fuzzy controllers [1], neural networks [2,3], etc. [4].…”
Section: Introductionmentioning
confidence: 99%
“…Such a system has a large traversing range and high accelerations can be reached in this arrangement. It is even possible to realize inverted pendulum consisting of two or three links [1].…”
Section: Introductionmentioning
confidence: 99%